The efficacy of virtual reality exposure therapy for the treatment of alcohol use disorder among adult males: a randomized controlled trial comparing with acceptance and commitment therapy and treatment as usual - Deng, Hongdu; Zhang, Ruiling; Wang, Chuansheng; Zhang, Bingyu; Wang, Jiali; Wang, Shilin; Zhang, Jie; Shari, Nurul Izzah; Leong Bin Abdullah, Mohammad Farris Iman (Frontiers in Psychiatry, 2023)
Background: This multicenter, three-armed, parallel, single blind randomized control trial (RCT) primarily aim to compare the efficacy of virtual reality exposure therapy (VRET) with that of acceptance and commitment therapy (ACT) and treatment-as-usual (TAU) to depreciate the degree of alcohol craving among alcohol use disorder patients who have undergo in-patient detoxification across four timelines (t0 = baseline prior to intervention, t1 = 4 weeks after baseline, t2 = 12 weeks after baseline, and t3 = 24 weeks after baseline). The secondary aims of this RCT are to compare the efficacy of VRET with that of ACT and TAU to alleviate severity of alcohol use disorder, dissipate co-morbid depressive and anxiety symptoms, and normalize event-related potential (ERP) in electroencephalogram (EEG) monitoring across the four timelines. Methods: Initially, after 2 weeks of in-patient detoxification, 120 patients with alcohol use disorder will be randomized into three groups (VRET, ACT, and TAU control groups) via stratified permuted block randomization in a 1:1:1 ratio. Baseline assessment (t0) commence whereby all the participants will be administered with sociodemographic, clinical, and alcohol use characteristics questionnaire, Alcohol Use Disorder Identification Test (AUDIT), Penn Alcohol Craving Scale (PACS), Hamilton Anxiety Rating Scale (HAM-A), and Hamilton Depression Rating Scale (HAM-D), while event-related potential (ERP) detection in electroencephalogram (EEG) will also be carried out. Then 4 weeks of VRET, ACT and non-therapeutic supportive activities will be conducted in the three respective groups. For the subsequent three assessment timelines (t1, t2, and t3), the alcohol use characteristics questionnaire, AUDIT, PACS, HAM-D, HAM-A, and ERP monitoring will be re-administered to all participants. Discussion: As data on the effects of non-pharmacological interventions, such as VRET and ACT on treatment of alcohol craving and preventing relapse in alcohol use disorder is lacking, this RCT fills the research gap by providing these important data to treating clinicians. If proven efficacious, the efficacy of VRET and ACT for treatment of other substance use disorder should also be investigated in the future. Trial registration: NCT05841823 (ClinicalTrials.gov). Registered on May 2, 2023.